Novos Medicamentos Apenas Disponibilizados a Nível Hospitalar: O Processo de Compra pelos Hospitais do SNS e a Avaliação Económica - Ana Teresa Paquete (Formifarma, LDA., 2013)
Introduction: The access to hospital use drugs (HUD) in the Portuguese National Health Service (NHS) hospitals is a two-stage decision process. The first stage is the reimbursement approval at the national level and the second stage is the purchasing decision by Drug and Therapeutic Committees (DTCs) of each NHS hospital. Objectives: To identify the most important factors considered by DTCs when deciding to buy a new HUD and to understand the utility of economic evaluation studies (EES) in this context. Methods: A postal survey was developed and sent to hospital pharmacy directors and clinical directors of all Portuguese NHS hospitals. Results: A response rate of 25% was obtained. Evidence on cost-effectiveness, safety, effectiveness and the lack of therapeutic alternatives were considered, on average, as more important factors than budget impact analysis or acquisition costs to consider in this decision-making process. The Prior Assessment Reports were chosen as the most important source of information used, with EES publications in sixth place. Among barriers and factors that could simplify the use of EES are the distrust on EES financed by the pharmaceutical industry and local needs as to consider more therapeutic alternatives and a hospital perspective in EES. Ethical objections to applying economic criteria in the decision-making process do not seem a barrier to use EES. Conclusions: This analysis allowed a foremost analysis about the decision-making process of introducing new HUD in Portuguese NHS hospitals, notwithstanding its limitations as the low response rate. Cost-effectiveness analyses were considered of higher importance to the decision-making process, with special reference to Prior Assessment Reports. However, there is a high distrust level on EES financed by the pharmaceutical industry. Some needs of local decision-makers were also identified. Including more therapeutic alternatives and a hospital perspective were stressed as their main specific needs.